Comparison and Translation: Towards a Combined Methodology for Contrastive Corpus Studies - Lavid, Julia; Arús, Jorge; Moratón, Lara (International Journal of English Studies, 2009)
This paper describes a methodology which combines the use of original comparable texts and bidirectional translations for the contrastive study of linguistic phenomena. The methodology is based on the following procedures: (1) analysis of the preferred linguistic choices in original comparable texts; (2) analysis of the preferred linguistic choices in original texts and comparison with those occurring in translations; (3) analysis of the translation strategies used in both directions of the translation process. As an illustration of the proposed methodology, thematic head choices in English and Spanish are analysed contrastively using original and translated texts from three different written genres. The paper discusses the advantages and the limitations of using original and translated texts and advocates a combined use of both types of data to enrich contrastive functional descriptions.